Fast three-dimensional time-of-flight magnetic resonance angiography: Should it be used in routine neuroimaging for headaches? - Ahmet Nedim, Kahraman; Vural, Ahmet (International Journal of Health Sciences, 2021)
Objectives: We aimed to evaluate the diagnostic efficacy of fast three-dimensional (3D) time-of-flight (TOF) magnetic resonance angiography (MRA) in the detection of cerebral aneurysms. Methods: We screened 1589 patients over a 3-year period, who underwent a magnetic resonance imaging for headache. Fast 3D TOF MRA images taken in addition to routine neuroimaging sequences, which were examined by two independent observers to assess cerebral aneurysms. Results: Sixty-nine aneurysms were detected in 63 patients. The locations of the aneurysms were as follows: Middle cerebral artery, 27.5% (n = 19); internal carotid artery, 53.6% (n = 37); anterior cerebral artery, 5.8% (n = 4); posterior cerebral artery, 5.8% (n = 4); anterior communicating artery, 5.8% (n = 4); and ophthalmic artery, 1.4% (n = 1). Thirty-five (50.7%) were 7 mm or less, 23 (33.3%) were 8–10 mm, and 11 (15.9%) were 11 mm or larger. About 88% of pathological cases (n = 61) were saccular and 12 (n = 8) were fusiform type aneurysms. The interobserver compliance was high (K = 0.83) for detecting the aneurysms. Conclusion: Considering the mortality and morbidity of subarachnoid hemorrhages, 3D TOF MRA is a successful, non-invasive method for detecting cerebral aneurysms. Results of the present study have shown that adding 3D TOF MRA to the routine brain imaging protocol is a beneficial tool for diagnosis.